2010
DOI: 10.1097/01.inf.0000366838.82857.78
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Coinfections in Lung Tissue Specimens from Fatal Cases of 2009 Pandemic Influenza A (H1N1) – United States, May–August 2009

Abstract: Background:To evaluate the impact of routine hepatitis B (HB) vaccination on the prevalence of chronic hepatitis B virus (HBV) infection among children in Pacific Island countries where HBV infection was highly endemic, we conducted HB serosurveys during 2000 to 2007 among women of childbearing age born before implementation of HB vaccination and among children born after its implementation. Methods: Serum specimens were collected from children aged 2 to 6 years and their mothers in Chuuk, Federated States of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…During influenza pandemics prior to that of 2009, bacterial coinfections caused by S. pneumoniae, H. influenzae, S. aureus, and group A streptococci significantly contributed to morbidity and mortality. 9,10 H. influenzae is a small gram-negative bacillus that can be part of the respiratory tract normal microbiome. When the bacterial cell membrane breaks, lipopolysaccharide is released, which is a molecule that participates in the inflammatory process and that in serum binds to lipopolysaccharide-binding proteins (LBP), a complex with high specificity to CD14.…”
Section: Introductionmentioning
confidence: 99%
“…During influenza pandemics prior to that of 2009, bacterial coinfections caused by S. pneumoniae, H. influenzae, S. aureus, and group A streptococci significantly contributed to morbidity and mortality. 9,10 H. influenzae is a small gram-negative bacillus that can be part of the respiratory tract normal microbiome. When the bacterial cell membrane breaks, lipopolysaccharide is released, which is a molecule that participates in the inflammatory process and that in serum binds to lipopolysaccharide-binding proteins (LBP), a complex with high specificity to CD14.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial superinfection is a known complication to influenza infections 5,6 . Studies have found an occurrence of bacterial superinfections following influenza ranging from 4% to 47% 6‐9 . Amongst the most common pathogens in bacterial superinfections are S pneumoniae , S aureus and H influenzae 10 …”
Section: Introductionmentioning
confidence: 99%
“…5,6 Studies have found an occurrence of bacterial superinfections following influenza ranging from 4% to 47%. [6][7][8][9] Amongst the most common pathogens in bacterial superinfections are S pneumoniae, S aureus and H influenzae. 10 Invasive pulmonary aspergillosis (IPA) is known to follow severe influenza especially in immunocompromised patients, but recent studies have shown that otherwise healthy patients are also at risk of invasive pulmonary aspergillosis infection.…”
mentioning
confidence: 99%
“…In addition, Streptococcus pneumoniae, Haemophilus influenzae and Staphylococcus aureus were frequently associated with NP and mortality in influenza pandemics 5 . It was estimated that approximately 29%-55% of the total 300,000 deaths in the 2009 H1N1 pandemic were caused by secondary bacterial NP 68 .…”
Section: Introductionmentioning
confidence: 99%